(untitled) (INNOVATIVE ECONOMY, 2025)
Pavlyshyn S.P. CURRENT TRENDS IN THE DEVELOPMENT OF THE GRAIN MARKET IN UKRAINE AND IN THE WORLD Purpose. The aim of the article is to investigate current trends in the grain market in Ukraine and globally, and to forecast its future development. Methodology of research. The theoretical and methodological principles of the research are: the dialectical method of understanding economic processes, fundamental principles of marketing, and scientific works of Ukrainian and foreign scientists on the problems of marketing research of the grain market situation. In the process of conducting scientific research, several special and general methods were used: monographic (in-depth study of the tasks set); theoretical comparison and generalization (with theoretical generalization and formation of conclusions); historical and retrospective (study of the grain market situation in Ukraine and the world); functional-cost and statistical analysis (survey of trends in the development of the grain market in Ukraine and the world, determination of its dynamics, structure, effectiveness of the activities of subjects of the agricultural sector of the economy of Ukraine); graphic (reflection of the results of research and marketing processes in the grain market), etc. The information base for the research was official data: the Verkhovna Rada of Ukraine, the Ministry of Agrarian Policy and Food of Ukraine, the State Customs Service, the State Statistics Service of Ukraine, the Ukrainian Agrarian Business Club, the Food and Agriculture Organization of the United Nations (FAO), etc.; information from the Internet, scientific articles, materials from scientific conferences, monographs and other scientific works of domestic and foreign scientists on current problems of marketing and marketing research of the grain market situation, results of surveys and questionnaires, own observations and research. Findings. The current trends of the grain market in Ukraine and the world, and their development forecast, were analysed. The key role of Ukraine as one of the leading global producers and exporters of agro-food products: corn, wheat, barley, sunflower, and rapeseed were substantiated. It was established that Ukraine is a key supplier of wheat to the world markets: The European Union (46%), Southeast Asia (16%), Asia (6%), as well as the Middle East (12%) and Africa (16%). It was proven that Ukraine is the third largest global exporter of corn: the share in the global export structure is 15%, and the specific weight in the global production structure is 2.5%. Ukraine is important as a leading supplier of non-GMO products (corn, rapeseed, and soybeans) to international markets and a key exporter of organic feed. As a result of Russia’s military aggression against Ukraine in the 2024/2025 MY compared to the 2021/2022 MY, the level of grain production and export decreased significantly: corn production decreased by 15.33 million tons (36.4%), export deliveries decreased by 4.98 million tons (18.5%); wheat production decreased by 9.6 million tons (29.1%), wheat exports decreased by 2.84 million tons (15.1%); barley production decreased by 4.12 million tons (41.5%), and its barley exports decreased by 10 thousand tons (0.4%). It has been established that Ukraine successfully uses the Black Sea ports (Chornomorsk, Odesa, and Pivdenny) to ensure grain export deliveries via logistics routes with the use of marine transport. It has been shown that in the 2024/2025 MY, the primary consumers of grain from Ukraine were the countries of the European Union, which imported about 50% of the total volume of grain exports from Ukraine (49% corn, 46% wheat, 42% barley). Originality. For the first time, the dependence of corn acreage and the level of profit of agricultural formations on logistics costs were substantiated. This allowed establishing a trend towards an increase in corn crops in Ukraine in the 2025/2026 MY, provided that stable export supply chains were established. The methodology for forecasting the development of the world grain market using FAO data was improved, which, unlike existing approaches, allowed for establishing trends towards a slowdown in the growth rate of world demand for grains, as production volumes are expected to increase due to an increase in the yield level. Based on the use of the specified methodology, it was proven that in the next decade, the rate of increase in demand for grains will slow down compared to the previous decade, mainly due to a slower growth in demand for feed for farm animals and poultry, and biofuels. The approaches to determining the correlation between consumer income levels and per capita consumption of grain crops for food purposes in several countries with high and medium levels of consumption have been improved, which made it possible to identify existing limitations for overall demand growth and trends in market saturation. Methodological principles for forecasting grain production have been further developed, which made it possible to establish trends for an increase in world production by 350 million tons to 3.2 billion tons in 2033, mainly due to the rise in corn and wheat production. At the same time, it is substantiated that Asian countries will provide about 40% of the growth of output, considering the trends observed over the past decade. The developed forecast demonstrates a trend for an increase in world corn production by 187 million tons to 1.4 billion tons by 2033, with the most significant increase in production occurring in the United States and China, followed by Brazil, Argentina, and India. The approaches to determining promising markets for corn exports from Ukraine for the period until 2033 have been improved, which, unlike the existing ones, consider the population growth rate and the importance of corn as a basis for nutrition in a particular country, which made it possible to establish the relevance of sub-Saharan African countries as priority sales markets. Practical value. The research results will allow the leaders of domestic agricultural formations to develop a marketing product policy, considering the trends in the world grain market and its conditions. Key words: grain market, corn, wheat, barley, production, yield, grain exports, grain market development trends, forecasting world grain market demand, supply, agri-food markets.